Functional comparison of MERS-coronavirus lineages reveals increased replicative fitness of the recombinant lineage 5 - Simon Schroeder (Nature Portfolio, 2021)
MERS-CoV is enzootic in dromedary camels, can spread to humans but undergoes limited onward transmission. Here, Schroeder et al. compare clinical isolates of MERS-CoV in vitro and show that the predominantly circulating recombinant lineage 5 possess a fitness advantage over parental lineage 3 and 4 due to reduced activation of innate immune signaling.